(untitled) (Research, Society and Development, 2022)
Objective: analyze and synthesize from the reading of scientific evidence available in the literature, how nursing care is given to cancer patients who are in a hospital environment in the context of the Covid-19 pandemic. Methodology: Integrative Literature Review based on the methodology proposed by the Joanna Briggs Institute. The following data sources were analyzed: Embase, CINAHL with Full Text, ScienceDirect, Cochrane Clinical Answers, Academic Search Premier, BVS, LILACS, BDENF Enfermagem and PubMed. The descriptors and Booleans used were: (Nursing) AND (2019 nCoV Disease) AND (Oncology Care) AND (hospital Care). Six scientific articles were included in the study. Results: Regarding the themes identified after analyzing the studies, four categories summarize the main aspects found: clinical organization, difficulties and nursing perceptions in the care of cancer patients in a hospital context; the impact of knowledge about Covid-19 on clinical practice; strategies for tracking suspected cases; and care for cancer patients diagnosed with the disease. Conclusion: It is essential that, in order to promote health and prevent the risk of this disease, through specialized education, nursing can find a favorable path, capable of implementing an efficient management of these patients. It is evident that, from the data collection, there is a lack of information on the subject. Therefore, it is necessary for nursing professionals who work in a hospital environment to provide the scientific community with information related to the challenges present in the care of these patients.